On shape dependence of holographic entanglement entropy in AdS4/CFT3 with Lifshitz scaling and hyperscaling violation - Giacomo Cavini; Domenico Seminara; Jacopo Sisti; Erik Tonni (Journal of High Energy Physics, 2020)
Abstract We study the divergent terms and the finite term in the expansion of the holographic entanglement entropy as the ultraviolet cutoff vanishes for smooth spatial regions having arbitrary shape, when the gravitational background is a four dimensional asymptotically Lifshitz spacetime with hyperscaling violation, in a certain range of the hyperscaling parameter. Both static and time dependent backgrounds are considered. For the coefficients of the divergent terms and for the finite term, analytic expressions valid for any smooth entangling curve are obtained. The analytic results for the finite terms are checked through a numerical analysis focussed on disks and ellipses.